Optimization of medium and cultivation conditions for D-lactic acid production using cassva starch [electronic resource] - Alsaheb, Ramzi Ata Abd., 1981-, author 642108; El-Enshasy, Hesham Ali Metawally Ali, supervisor 642109; Fakulti Kejuruteraan Kimia dan Kejuruteraan Tenaga 599090 (2016)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2016